Holistic Development of Agroforestry in India and the Key Factors for Success - Lal, Piare (Indian Forester, 2020)
Agroforestry plantations currently meet nearly 90% of industrial round wood requirements of major wood based industries such as plywood and panel products and pulp and paper. Moreover agroforestry contributes immensely to dense forest and tree cover of India, carbon sequestration and climate change mitigation, increase in employment opportunities and government revenues and indirect conservation of natural forests. This paper discusses key factors that contribute to the success of major agroforestry projects, issues, constraints, opportunities and policy reforms required for holistic development of agroforestry in India and makes specific suggestions for consideration of government and the stake holders.